PROFILE PENERIMAAN ORANG TUA ANAK BERKEBUTUHAN KHUSUS DI PUSAT LAYANAN TUMBUH KEMBANG RUMAH KUNANG-KUNANG MEMPAWAH - Neneng Sulasmi (CV. ADIBA ASIHA AMIRA, 2026)
Parental acceptance of their child’s special needs is a key factor influencing the success of the child’s growth and development. Parents who are able to accept their child’s condition tend to be more active in providing support, participating in therapy programmes, and creating an environment conducive to the child’s development. This study aims to identify the profile of parental acceptance among parents of children with special needs at the Rumah Kunang-Kunang Growth and Development Service Centre in Mempawah. This study aims to describe the acceptance profile of parents of children with special needs at the Rumah Kunang-Kunang Developmental Services Centre in Mempawah. The focus of the study includes parents’ initial emotional responses upon learning of their child’s condition, the factors influencing the acceptance process, and the stages of acceptance they go through until they are able to become a support system in their child’s therapy and education. The study employed a descriptive qualitative approach, utilising data collection techniques such as in-depth interviews, observation and documentation. The research informants comprised parents of children with special needs who accompanied their children whilst they participated in therapy and educational programmes at the Rumah Kunang-Kunang Developmental Centre in Mempawah. Data analysis utilised the Miles and Huberman model through data reduction, data presentation and drawing of conclusions. The results of the study indicate that the majority of parents experienced phases of denial, sadness, anger, guilt and anxiety before reaching acceptance. Family support, adequate information, religious beliefs, positive therapeutic experiences and the child’s development were the main factors facilitating the acceptance process. A positive level of acceptance was characterised by increased parental involvement in therapy, education and advocacy for the child’s needs.